Modelo de gestión con enfoque de responsabilidad social para microempresas. Estudio de caso empresa Reyursa S.A Machala Ecuador - Edith Marlene Rogel Gutierrez; Juan Isaac Urquizo Villafuerte; Cesar Javier Quezada Abad; Eduardo Antonio Muñoz Jácome (European Scientific Journal, ESJ, 2016)
Today, corporate social responsibility considers social, environmental and economic factors, ethical values, people, communities and the environment. ISO 26000 promotes decision making for the benefit of society, reduces the labor risk, contributes to public confidence, it generates innovation and business competitiveness, strengthening ties with its stakeholders, maximizing loyalty of its employees minimizes conflicts with consumers. The main beneficiaries of Corporate Social Responsibility are stakeholders (shareholders, employees, suppliers, customers, community and environment). Moreover, the design and implementation of the management model of Corporate Social Responsibility in micro, is not only a priority, but a strategic decision of vital importance, seeking economic, social, environmental well-being from the company and to the community. A level micro business in Ecuador CSR is not evident, so it became necessary research to meet the situational state of CSR and from the same generate a model for this group of companies based on the case study company Reyursa SA , representative at the level of the city of Machala, province of El Oro, Ecuador, becoming a sample of what is happening and what you can do for microenterprises in similar conditions, also contributing to the control mechanisms microenterprise to ensure timely and fair payment of wages and profits; generate awareness actions and respect for human rights; promote a culture of respect for nature; develop and implement good social and environmental practices; promote integrated processes and citizen campaigns to promote environmental awareness and ethical aspects related to the Plan of Good Living in Ecuador from 2013 to 2017.